A Century of Physics - Bromley, D. Allan. author. aut Link
X, 114 p. 128 illus., 41 illus. in color.
Keywords: In this amazing tour d'horizon, D. Allan Bromley uses the occasion of the centenary of the American Physical Society to reflect upon the growth of physics over the past 100 years, its fragmentation into numerous subdisciplines, the impact physics has had upon modern technology, and the re-emergence of the fundamental unity of the discipline in recent years. Hundreds of historical illustrations accompany the text. Bromley conveys much of the excitement and wonder that research in physics generated in the 20th century and asks what new things are in store in the next century. He covers such topics as relativity and quantum mechanics, the Manhattan project, superconductivity, transistors and the revolution brought about by solid-state electronics, protein folding, the uses of nuclear and atomic physics in biology and medicine, plate tectonics, the expansion of the universe and the Big Bang, and gravitational radiation. Bromley, the Sterling Professor of the Sciences and Dean of Yale University, served as Assistant to the President for Science and Technology Policy 1989-1993 and was president of the American Physical Society in 1997. One of the World's leading nuclear scientists, he was founder and director of Yale's nuclear structure laboratory and has received numerous medals and awards, including the National Medal of Science.